What is Outcome Harvesting? - Wilson-Grau, Ricardo (2014)
Ricardo Wilson-Grau, former Chair of the Board of Stewards of the Outc ome Mapping Learning Community, introduces Outcome Harvesting, an appr oach for retrospective identification of outcomes based on the princip les of Outcome Mapping. More details here: http://www.outcomemapping.c a/nuggets/outcome-harvesting